The Role Of E-Learning In Disseminating Environmental Education Concepts Among University Students In Iraq (Journal of the College of Basic Education, 2024)
The research aimed to identify the role of e-learning in disseminating the concepts of environmental education among Iraqi university students from the point of view of the educational staff there. The descriptive analytical method was adopted. The study sample consisted of (186) faculty members who were randomly selected from the educational staff at the University of Baghdad / College of Education / Ibn Al-Haytham. (14) individuals were excluded due to their lack of response or leaving some questions unanswered, so the sample became composed of Of (172) members of the educational staff from the Ibn al-Haytham College of Education at the University of Baghdad, the study tool was a questionnaire that dealt with the two variables (e-learning, environmental education). The validity and reliability of the questionnaire was confirmed by appropriate statistical methods, and arithmetic means and standard deviations were used to extract Results. The study reached many results, the most important of which is the existence of a major role for e-learning in disseminating the concepts of environmental education among Iraqi university students. It also found that there are no statistically significant differences between members of the educational staff according to the variables of gender, academic qualification, and teaching experience.